Shooting Accuracy of Sports Coaching Education Students: Goaling Game Practice - Mappaompo, M. Adam; Aprilo, Ians; Arga, Arga; Arfanda, Poppy Elisano (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aimed to determine the effect of goal-setting game training and how effective it is in improving the shooting accuracy of extracurricular students at UPRI Sports Coaching Education. This study is an experimental design, involving two training groups throughout 16 meetings, one serving as a pretest and another as a posttest. We conducted this study for approximately one month to investigate the impact of goal-game training on the shooting accuracy of UPRI Sports Coaching Education students participating in extracurricular activities. The results demonstrated a significant impact of goal-setting game training on shooting accuracy, as evidenced by a statistical increase in the average pretest shooting accuracy from 25.80 points to 42.30 points for the treatment group and from 26.50 points to 33.20 points for the control group. The hypothesis test's significance value is less than 0.05. The conclusion is that goal-game training affects the shooting accuracy of extracurricular UPRI Sports Coaching Education students.